EFFECT OF BEARING DIAMETER OF BOLT HEAD ON INTERFACIAL PRESSURE IN BOLTED JOINTS - J. T. STEPHEN; A. ADEBAYO; G.J. ADEYEMI (International Journal of Innovations in Engineering Research and Technology, 2018)
The proper selection of the bolted joints is very important factor. The contact pressure distributed is the key factor behind success of the interfacing. The consideration of the contact pressure during the design makes it possible to have successful integrity.The problems faced due to the theoretical analysis and the absence of the practical or experimental analysis leads to failure of the proper distributionof the pressure.Authors worked on the ultrasonic applications to understand the pressure distribution at the interface.The load considered is axial for the experiment.With increase in the load,the contact pressure increases. In bolted joints, the constant distribution point dose not depends on the load.